Asset commonality, debt maturity and systemic risk - Allen, Franklin; Babus, Ana; Carletti, Elena (Journal of Financial Economics, 2012)
We develop a model in which asset commonality and short-term debt of banks interact to generate excessive systemic risk. Banks swap assets to diversify their individual risk. Two asset structures arise. In a clustered structure, groups of banks hold common asset portfolios and default together. In an unclustered structure, defaults are more dispersed. Portfolio quality of individual banks is opaque but can be inferred by creditors from aggregate signals about bank solvency. When bank debt is short-term, creditors do not roll over in response to adverse signals and all banks are inefficiently liquidated. This information contagion is more likely under clustered asset structures. In contrast, when bank debt is long-term, welfare is the same under both asset structures.